Stronger microbial nutrient limitations in subsoil along the precipitation gradient of agroecosystem: insights from soil enzyme activity and stoichiometry - Yang, Jingjing; Guan, Pingting; Zhang, Peng; Wu, Yunga; Wang, Deli; Wu, Donghui (Frontiers in Ecology and Evolution, 2023)
Soil extracellular enzymes are central in terrestrial ecosystem responses to climate change, and their research can be crucial for assessing microbial nutrient demand. However, the effects of climate-induced precipitation patterns on soil microbial nutrient demand in different soil profiles of agroecosystems are rarely studied. Here, we present how the precipitation gradient affects soil enzymes related to carbon (C), nitrogen (N) and phosphorus (P) cycling and identified microbial nutrient limitation determinants at five depth intervals (0-10, 10-20, 20-30, 30-40 and 40-50 cm) in seven agroecosystems. We found that N- and P- acquiring enzymes have a tendency to increase or decrease, but C- acquiring enzymes did not change along the precipitation gradient throughout soil profiles. Soil pH and moisture were the most important factors affecting the enzyme activity in 0-50 cm. Our results also revealed a crucial soil boundary (at 20 cm) that differentiated responses of microbial nutrient limitation to precipitation changes. In the topsoil (0-20 cm), the stoichiometry of soil nutrients did not vary with precipitation. Microbial P limitation was exacerbated with increased precipitation, which was controlled by soil pH and moisture in the topsoil. In contrast, in the subsoil (20-50 cm), soil nutrient stoichiometry decreased with increasing precipitation, and microbial C and P limitation displayed a positive correlation with precipitation. Furthermore, microbial P limitation tended to be stronger in the subsoil than in the topsoil along the precipitation gradient. Microbial C and P limitation was regulated by the soil nutrients and their stoichiometry in the subsoil. Our study is an essential step in soil enzyme activity and stoichiometry response to precipitation in agroecosystems and provides novel insights into understanding microbial nutrient limitation mechanisms in soil profiles along the precipitation gradient.